Aye-aye population genomic analyses highlight an important center of endemism in northern Madagascar - Jr., Edward E. Louis (2014)
We performed a population genomics study of the aye-aye, a highly specialized nocturnal lemur from Madagascar. Aye-ayes have low population densities and extensive range requirements that could make this flagship species particularly susceptible to extinction. Therefore, knowledge of genetic diversity and differentiation among aye-aye populations is critical for conservation planning. Such information may also advance our general understanding of Malagasy biogeography, as aye-ayes have the largest species distribution of any lemur. We generated and analyzed whole-genome sequence data for 12 aye-ayes from three regions of Madagascar (North, West, and East). We found that the North population is genetically distinct, with strong differentiation from other aye-ayes over relatively short geographic distances. For comparison, the average FST value between the North and East aye-aye populations—separated by only 248 km—is over 2.1-times greater than that observed between human Africans and Europeans. This finding is consistent with prior watershed- and climate-based hypotheses of a center of endemism in northern Madagascar. Taken together, these results suggest a strong and long-term biogeographical barrier to gene flow. Thus, the specific attention that should be directed toward preserving large, contiguous aye-aye habitats in northern Madagascar may also benefit the conservation of other distinct taxonomic units. To help facilitate future ecological- and conservation-motivated population genomic analyses by noncomputational biologists, the analytical toolkit used in this study is available on the Galaxy Web site.